(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This study investigates the intricate tension between society and the self through an ideological lens, focusing on motivational constructs in the literature of Said Ahmad and George Orwell. By examining the ethical, cultural, and political determinants that shape character behavior, the research highlights how external societal pressures and internal psychological drives interact to influence decision-making and action. Said Ahmad’s narratives emphasize moral responsibility, cultural identity, and social conformity, revealing the subtle ways in which collective norms mediate individual choices.